Estratégias de leitura e seus efeitos na aprendizagem sobre o teorema de Tales de Mileto : um estudo com alunos da rede pública estadual de Sergipe - Conceição, Fábio Henrique Gonçalves (2019)
Authors such as Kleiman (2012) and Solé (1998) argue that reading strategies are necessary procedures for understanding a text. This text can be written in mathematical language. By taking into account this fact and the relevance of presenting researches whose results allow improvements to the mathematical learning process of the subjects, we developed this study, proposing to investigate the effects of the reading strategies in the learning about the theorem of Thales of Miletus. This objective arose from the following question: What are the effects on the use of reading strategies in learning about the Tales of Miletus theorem of 9th grade students enrolled in the state public school system in Aracaju-SE? In order to fulfill the purpose of this study, we developed an investigation that, in its methodological aspects, was configured as a qualitative research, epistemologically, based on the studies of Piaget (1977, 1978), Solé (1998), Charlot (2000, 2005, 2013), among others. As for the procedures, the field research was adopted, whose nature is exploratory and analytical descriptive. As a research field, two schools of the state public network of Sergipe, located in Aracaju-SE, were selected, counting on the participation of 14 students enrolled in classes of the 9th grade of elementary school in these schools, as subjects of the research. To do so, we adopted as criteria that the respective responsible of these students authorized the participation, so that each one, when participating, carried out all the activities developed during the meetings. To obtain the data, we performed three stages, the first and last with application of: an adaptation to the balance of knowledge, diagnostic activity and interview. The second stage was a process of intervention, by which it was possible to verify that, in general, the reading strategies contribute to develop in the student, the necessary skills to learn to learn. The results also point out that the teaching work with reading strategies in activities on the Tales of Miletus theorem allows students to demonstrate a sense of learning, knowing how to do and understanding what they are learning. In addition, we observed that the reading strategies interfered in the students' awareness to solve problems about the said theorem; as well as, there was mobilization, by the investigated, to resolve the activities with effective procedures. This is due to the fact that there has been a rupture with the memorization of procedures so marked in the initial discourses of these students. The results highlighted in this study also indicate that reading strategies can be used as a favorable element to mathematical learning, in particular in this research, regarding the Thales of Miletus theorem.